2022
DOI: 10.3390/ijerph19053046
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanism of Government–Industry–University–Institute Collaborative Innovation in Green Technology Based on Game–Based Cellular Automata

Abstract: In order to ensure stable cooperation among the government, enterprise and university/institute in the green technology innovation process and guide an increasing number of innovation agents in the region to adopt cooperation, this paper studies the mechanism of green technology innovation. A tripartite evolutionary game model is established and the strategy choices of the government, industry and university/institute are analyzed through mathematical derivation. On this basis, the cellular automata theory is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Such a high and appropriate government subsidy F = 0.1 is possible for institutions in real life and consistent with the real situation. Summing up, the government subsidy F can make the average in-probability and out-probability rise through the evolution of the game, while government subsidies F are unlikely to be large, an appropriate subsidy coefficient can strengthen the cooperative relationship in the innovation project [42]. The government can promote patent cooperation without providing very high subsidies, which also be found in section IV-A.…”
Section: Influence Of Wages and Government Subsidymentioning
confidence: 86%
“…Such a high and appropriate government subsidy F = 0.1 is possible for institutions in real life and consistent with the real situation. Summing up, the government subsidy F can make the average in-probability and out-probability rise through the evolution of the game, while government subsidies F are unlikely to be large, an appropriate subsidy coefficient can strengthen the cooperative relationship in the innovation project [42]. The government can promote patent cooperation without providing very high subsidies, which also be found in section IV-A.…”
Section: Influence Of Wages and Government Subsidymentioning
confidence: 86%
“…With the increase in m, the enterprise can only obtain limited green credit support. Therefore, to reduce the costs and risks of innovation, the CDW recycling enterprise chooses collaborative innovation (Li & Zhou, 2022).…”
Section: Numerical Simulation and Discussionmentioning
confidence: 99%
“…CDW recycling enterprises have two green technology innovation modes: independent innovation and collaborative innovation (Li & Zhou, 2022). Collaborative innovation is an innovation mode in which members of an organization respect and trust and share risks and resources to realize goals .…”
Section: Green Technology Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Junmin Wu et al studied the new mechanism of collaborative innovation in the post-subsidy era, indicating that the status of the government should be transformed from a coordinator to a vital participant and its functions should be changed from guidance, coordination, and supervision to supervision and incentive [8]. Based on cellular automata theory, Tuochen Li and Xinyu Zhou concluded that increasing cooperative innovation income distribution fairness can consolidate industry-university collaborative innovation cooperation [9]. Karolin Sjoo and Tomas Hellstrom summarized seven factors that affected industry-academia collaborative innovation and discussed the degree of government policy intervention in aspects [10].…”
Section: Introductionmentioning
confidence: 99%